EFL STUDENT TEACHERS’ EXPERIENCES WITH AI-ASSISTED LESSON PLANNING - Fika Megawati; Sheila Agustina; Abayeva Akniyetnessibeli (Academic Journal Research, 2026)
Objective: Artificial Intelligence (AI) is increasingly transforming English language teaching, yet its potential to integrate technology, moral values, and authentic content in pre-service teacher education remains underexplored. This study investigates how pre-service English teachers utilize AI to design culturally and morally grounded lessons. Method: Adopting a quantitative descriptive approach, data were collected via an online survey from 34 undergraduate students enrolled in a Microteaching course at a private university in Indonesia. The instrument comprised open-ended questions on AI use, integration of Islamic moral values, and selection of authentic materials. Results: Results show that ChatGPT was the most frequently used tool, followed by Gemini. Participants employed AI to source learning materials, recommend teaching strategies, generate quizzes, and adapt lessons to learner needs. Moral values were embedded through ethical guidance, social responsibility, prayer rituals, and spiritual reflection. AI-suggested authentic content was incorporated to enhance contextual relevance but was selectively adapted to align with cultural and personal values. Findings demonstrate that AI substantially enhances lesson planning by streamlining resource selection and fostering pedagogical creativity, while preserving the teacher’s role as a cultural and ethical filter. Novelty: This study highlights AI’s dual potential—as an innovative pedagogical partner and as a tool requiring critical oversight—to ensure language instruction that is technologically enriched, culturally responsive, and value-oriented.